(untitled) (Comparative & International Education Series, 2022)
Completing a doctorate changes people in different ways. Among factors that shape the experience and success of PhD students, supervisors and supervision practices play the most important role. Although there are some studies on the relationship between supervisors and supervisees, the supervisees’ experiences as students and later as supervisors remain unexplored. Using positioning theory, this chapter aims to address the gap by interviewing five Vietnamese university teachers about their perceptions of the supervisory relationship as international doctoral students and then as supervisors. Findings show both the embracement and adaptation of the participants in their supervision practices as a result of shifting academic and cultural differences between the host and home countries. The study would contribute to a better understanding of the role that doctoral experiences play in supervisors’ development.